Rozwój rynku usług logistycznych w Polsce w latach 2008-2011: The development of logistics services in Poland in 2008-2011 - Pieniak-Lendzion, Krystyna (Management and Administration Journal, 2021)
Currently in Poland, a supply of logistics services has been increased. There is a wide diversity of services, which are offered by companies operating in the TSL sector. The companies are different in size, structure of the organization and type of ownership. There are manycompanies which provide only one type of logistics services e.g. storage, transport and shipping. In the TSL there are also companies offering a wide variety of logistics services. In Polandthe TSL sector is still changing. Small companies are merged into one big company in order toincrease their potential and gain a competitive advantage. It is noticed that clients of TLS sectormore and more often choose companies which offer a wide variety of logistics services. Thiscompanies help to solve problems of their clients in more comprehensive and efficient way. Thegrow of storage space for rent is the result of the growing popularity of comprehensive services.Clients of the TLS sector also indentify a lot of benefits in connection with involvement of an external supplier.